Electro‐mechanical deformation of amorphous and semi‐crystalline polymeric films. Issue 40 (15th March 2020) - Zhang, Ci; Li, Zhenpeng; Nian, Haofei; Zhu, Lei; Olah, Andrew; Baer, Eric
Abstract: In our previous study, electrically induced mechanical stress was produced on monolithic polycarbonate (PC) films under a DC voltage using a needle‐plane electrode setup. This study investigated other materials with various structures and dielectric constants, in order to further understand the deformation mechanism. It was found that the elastic behavior occurred at electric fields intensities below that initiating measurable surface deformation. The amorphous materials, PS, and the semi‐crystalline materials, HDPE and PP, having dielectric constants all around 2.5, exhibited a similar observable deformation onset electric field at 200 MV/m. While PVDF, having a dielectric constant of 10.0–12.0, showed an onset at only 30 MV/m. The data was also compared to our previous study on PC. The depth and diameter of the deformation for all materials increased relative to the applied electric field up to film breakdown. Thermal annealing of the deformed films revealed a recoverable "delayed elastic" component and an irreversible "plastic" component. A three‐stage electrically induced mechanical deformation mechanism was proposed for amorphous materials, while a two‐stage mechanism was proposed for the semi‐crystalline materials. The difference on the energy loss versus deformed volume for amorphous and semi‐crystalline polymers was also determined and discussed. Abstract :